Land Management and Soil Quality in Sago-Based Agroforestry System: A Study on Mooi Tribe’s Ecological Knowledge (Sorong, Southwest Papua) and Modern Ecological Knowledge (MEK) - Wulandari, Diah Kartika; Hairiah, Kurniatun; Prayogo, Cahyo (Journal of Applied Agricultural Science and Technology, 2023)
Sago farmers from the Mooi tribe in Sorong Regency - Southwest Papua have consumed and cultivated sago for generations. This research aims to understand the local ecological knowledge (LEK) of sago farmers in managing their land to maintain soil quality in sago agroforestry, compared with modern/scientific environmental understanding. The survey was conducted from February to October 2021 in three sub-districts, Sorong Regency, using an exploratory descriptive method among Mooi sago farmers. Intact soil samples were taken to measure soil physical properties and disturbed soil samples to analyze soil chemical properties (pH, C-Organic, Total N, P, K, CEC, base saturation). The results of this research show that what sago farmers have in common with the unique habits of the Mooi tribe's harvest system is that they harvest enough sago starch to consume or sell if there is too much of it. According to sago farmers, the best land for growing sago is close to a water source and is not affected by soil biota and fertilization. and sago farmers will leave ella sago dregs on the land. Meanwhile, according to MEK, starch formation decreases in flooded land and the remaining sago dregs are very good for making compost and animal feed. In sago forests where sago grows naturally, the soil texture is dominated by silt, having a pH of 5.8-7.2; High total organic C 2.8-5.2%, P 14.08-66.44 mg/kg, K 755.3 – 1626.8 mg/kg, CEC 18-40 cmol(+)/kg, and base saturation 30 – 134%. These values are relatively higher than on land with a sago-based agroforestry system.